Occupational fatigue, individualized nursing care, and quality of nursing care among hospital nurses. Issue 5 (15th February 2022) - Cho, Hyeonmi; Sagherian, Knar; Scott, Linda D.; Steege, Linsey M.
Abstract: Purpose: This study aimed to evaluate the relationships among nurse fatigue, individualized nursing care, and nurse‐reported quality of care. Design: The study used a cross‐sectional design. Data from 858 registered nurses providing bedside care in hospitals were collected between March and April 2021 in the United States. Methods: Participants completed a self‐administered online survey, including the Occupational Fatigue Exhaustion Recovery scale, the Individualized Care Scale‐Nurse version, and a single item assessing nursing care quality. Relationships among the study variables were examined using multiple linear and logistic regression models. Findings: Nurses' higher levels of acute fatigue were significantly associated with decreased perceptions of individualized nursing activities provided to patients on their last shifts, specifically related to personal life condition and decision‐making control. Nurses' higher levels of chronic fatigue were significantly associated with decreased perception of individualized nursing activities provided to patients on their last shifts related to clinical condition, personal life condition, and decision‐making control. Nurses with higher levels of acute or chronic fatigue, and who perceived their nursing care activities as less individualized were less likely to assess their quality of care as excellent. Conclusion: These findings suggest that addressing hospital nurses' acute and chronic fatigue may contribute to promoting the delivery of individualized nursing care and in improving patients' quality of care. Clinical Relevance: Healthcare institutions are encouraged to regularly monitor and manage nurse fatigue to improve the delivery of individualized and quality nursing care to their patients.